EFFECTIVENESS OF CONTEXTUAL LEARNING IN ISLAMIC RELIGIOUS EDUCATION LESSONS AT SMA - Nurmawati Nurmawati; Usiono Usiono; Elis Ariska (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
The purpose of this study is to determine the inhibiting factors for the implementation of contextual learning in Islamic religious education subjects related to dressing according to Islam at SMA Kartika I-2 High School Medan Helvetia District, then to determine the supporting factors for implementing contextual learning in Islamic religious education subjects related to the implementation of contextual learning in Islamic religious education subjects SMA Kartika I-2 High School Kecamatan Medan Helvetia, and the last one is to find out the performance of contextual learning on Islamic religious education subjects at SMA Kartika I-2 High School Kecamatan Medan Helvetia. This type of research is qualitative research with a case study approach, namely research that seeks to describe events in the field as they are. And data collection techniques used are interviews, observation, and documentation. The primary sources in this research are Islamic religious education teachers at SMA Kartika 1-2 Medan. Data analysis using the Miles and Huberman model includes data collection, data reduction, data presentation, and concluding (verification).Keywords: Implementation of Contextual Learning.